Afro Memory, Identity, Territoriality and museological Spaces (Cadernos de Sociomuseologia, 2017)
This article aims to propose some reflections about memory, identity, territoriality and the importance of afros memorials in communities afro as a form of political strategy of a new scenic and textual language in the preservation, dissemination and re - readings of the memories projected in these spaces.Keywords: memory, identity, museum spaces.